2021
DOI: 10.3389/fphy.2021.665399
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Roles of Money Laundering in Bitcoin Mixing Transactions: A Goal Modeling and Mining Framework

Abstract: Cryptocurrency has become a new venue for money laundering. Bitcoin mixing services deliberately obfuscate the relationship between senders and recipients, making it difficult to trace suspicious money flow. We believe that the key to demystifying the bitcoin mixing services is to discover agents’ roles in the money laundering process. We propose a goal-oriented approach to modeling, discovering, and analyzing different types of roles in the agent-based business process of the bitcoin mixing scenario using his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…While it has been shown that it is relatively easy to identify CoinJoin transactions (Stütz et al, 2021), a protocol commonly used in popular decentralized Bitcoin mixers, it is, to the best of my knowledge, not easy to identify the mixing service that executed an identified CoinJoin transaction. Liu et al (2021) propose a framework that could potentially be used to estimate the scale of money laundering in a Bitcoin mixing service. They identify that various categories of addresses within a mixing transaction process can be classified as different agents with their own respective goals.…”
Section: Taking Down a Mixing Servicementioning
confidence: 99%
See 1 more Smart Citation
“…While it has been shown that it is relatively easy to identify CoinJoin transactions (Stütz et al, 2021), a protocol commonly used in popular decentralized Bitcoin mixers, it is, to the best of my knowledge, not easy to identify the mixing service that executed an identified CoinJoin transaction. Liu et al (2021) propose a framework that could potentially be used to estimate the scale of money laundering in a Bitcoin mixing service. They identify that various categories of addresses within a mixing transaction process can be classified as different agents with their own respective goals.…”
Section: Taking Down a Mixing Servicementioning
confidence: 99%
“…Liu et al (2021) propose a framework that could potentially be used to estimate the scale of money laundering in a Bitcoin mixing service. They identify that various categories of addresses within a mixing transaction process can be classified as different agents with their own respective goals.…”
Section: Addressing Laundered Bitcoin In Mixed Transactionsmentioning
confidence: 99%
“…Wu et al (2022) focus on the identification of addresses belonging to mixing services by analyzing transaction network patterns. Liu et al (2021a) propose a modeling framework for discovering and analyzing the roles of the agents in Bitcoin mixing services. The authors describe a case study in which their model helped in finding and characterizing the agents involved in a Bitcoin money laundering scenario.…”
Section: Background and Related Workmentioning
confidence: 99%